HEUTAGOGICAL APPROACH ON ENGLISH FOR JOURNALISM SUBJECT BY UTILIZING REMOTIVI YOUTUBE CHANNEL AS STUDY RESOURCE ON ENGLISH EDUCATION STUDENTS OF ISLAMIC INSTITUTE OF MUHAMMADIYAH SINJAI - Andi Muammar Kareba; Harmilawati Harmilawati; Andi Muhamad Zulfikar (UICELL, 2021)
As the students raised in the internet era, it is urged to serve them different kinds of study approach that involve the students as the core of the study, especially for those who learn in university. This research involved heutagogical approach to observe the way students explore their own learning style by using Youtube specific channel, Remotivi, that provides the students the different sides of mainstream media. This research aims to find out the application of heutagogical approach on English Education 7th-semester students who took English for Journalism subject which is an optional subject. This research is a qualitative study with a narrative descriptive approach that was conducted in English Education students of Islamic Institute of Muhammadiyah Sinjai. The data analysis technique is based on Miles and Huberman theory with observation sheets, interview guide, and documentation as instruments of collecting data. The results showed that 31 students who took English for Journalism subject and used Remotivi as their study resource could widen their perspective about journalism and encourage them to stay vigilant about stereotypes of what mainstream media have framed out. The students also found that heutagogical approach in this subject helped them to vary their way to study because they become delighted to absorb new information in different learning styles by the enchanting visual presentation of Remotivi channel. Keywords: heutagogy, English students, journalism, learning approach, Remotivi